2022
DOI: 10.3390/su14159474
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Sustainable Approach to Determining the Deployment Priorities of Automatic Vehicle Identification Sensors

Abstract: Monitoring vehicles’ paths is important for the management and governance of smart sustainable cities, where traffic sensors play a significant role. As a typical sensor, an automatic vehicle identification (AVI) sensor can observe the whereabouts and movements of vehicles. In this article, we introduced an indicator called the deployment score to present the deployment priorities of AVIs for a better reconstruction of vehicles’ paths. The deployment score was obtained based on a programming method for maximiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A case in Shanghai showed that the proposed method was superior to other algorithms. Li et al [12] introduced a deployment score indicator to present the deployment priorities of AVI sensors for a better reconstruction of vehicles' paths. Then, a random work method was developed to simulate massive path data, and a path-level bi-level programming model (P-BPM) was constructed to find the optimal layout of the AVI sensors for each simulated path.…”
Section: Introductionmentioning
confidence: 99%
“…A case in Shanghai showed that the proposed method was superior to other algorithms. Li et al [12] introduced a deployment score indicator to present the deployment priorities of AVI sensors for a better reconstruction of vehicles' paths. Then, a random work method was developed to simulate massive path data, and a path-level bi-level programming model (P-BPM) was constructed to find the optimal layout of the AVI sensors for each simulated path.…”
Section: Introductionmentioning
confidence: 99%